Barack obama : the making of man - Maraniss, David ([S.l.] : Atlantic, 2012)
In Barack Obama, David Maraniss has written a sweeping narrative which reveals the real story of Obama's beginnings: child of a black man from Luoland and a white woman born in Texas. He charts the fortunes of the two disparate families, polar opposites in every way, which produced these two extraordinary individuals, who met briefly in Hawaii, never cohabited, and married only to legitimize the child born of that union. At the heart of Obama's psyche and his political beliefs - and therefore his presidency - is his life-long struggle to understand the extreme duality of his identity. Maraniss explores his extraordinary journey from a mixed race boy raised by white grandparents in laid-back Hawaii to an African America with a burning political vision and vocation. Barack Obama contains a wealth of new material. Maraniss reveals here previously unpublished love letters written by Obama as a young man in a search of an identity: black or white, writer or a man who could lead. He also includes the journal entries of Obama's first significant (white) girlfriend, which chart their intense relationship and the moment when young Barack realized that he must leave everything behind him and set out for Chicago in order to 'become' an African American. The story wrought here is one of fierce ambition, survival, and love.